Growth kinetics and purifying performance of A. Platensis in stirring-free culture based on brewery effluent’s supernatant - LIADY, MOUHAMADOU NOUROU DINE; ADANDE, Richard; AKOWANOU, Akuemaho Virgile Onésime; Adjahouinou, Mahoussi Euphrasie; Goussanou, Baruc Kpèhouénou; Ahondokpè, Cécilia; Zouhir, Fouad; Kouadio, AROUNA; AÏNA, MARTIN PÉPIN (My University, 2022)
Due to costs of setting up and operating electrical stirring systems to keep algae in suspension and exposed to light, cultivation of mono- specific algae is poorly expanded in developping countries. However, some algal species such as Arthrospira platensis, are equipped with gaseous vesicles that allow them to stay afloat and increase their exposure to light. In this study, we investigated in an unstirred outdoor environment, its growth kinetic and purifying performance in a brewery effluent-based media. Batch cultures were carried out in three exper- imental treatments and evolution of physicochemical and growth parameters were monitored. Then its contribution to depollution was determined. Results show that optimal conditions for producing A. platensis include the culture tank transparency, the effluent dilution (i.e. 10%), and the culture media amendment with sodium bicarbonate and sodium nitrate. The average productivity recorded reached 0.55 g DW·L1·d1 during the exponential growth phase, while preserving culture from contamination. COD and total Nitrogen concentrations were reduced for 32.5% and 64.91%. Such results open up prospects for low-cost production of certain algae, in transparent and relatively high barrels, thus breaking, the classic barriers related to shallow basin depth and mechanical agitation traditionally considered as critical to the success of algal production.
Keywords: Arthrospira. platensis; brewery effluent; transparent tank; valorization; wastewater treatment